Computational intelligence : revised and selected papers of the International Joint Conference, IJCCI 2013, Vilamoura, Portugal, September 20-22, 2013 /: revised and selected papers of the International Joint Conference, IJCCI 2013, Vilamoura, Portugal, September 20-22, 2013. (2015) - Unknown
No abstract available